Pussy proofed. - Hibbs, Sarah; Pinder, Lola ([Melbourne, Vic.] : [publisher not identified], 2017)
A homage to female figures of punk.
Toilet / Elizaveta Malsteva -- Baroness Elsa & The Punk Archive / Alys Moody -- Jeanne d'Arc / Lola Pinder -- ECO/FEM / Elyse Goldfinch -- My calamity / Angelica Neville -- Mixed tape / Violet Nightingale -- Her boyfriend's a hairdresser / Megan Hales -- Pink on the inside / Violet Nightingale -- Kate Just chats to Nikita Holcombe -- Fowles in the frith / Ainslie Templeton -- Postcard on Pussy Riot / Phoebe Clarke -- God save the Queen / Sarah Hibbs & Amelia Elizabeth -- Max fill / Theia Connell -- Betty Davis, if I'm in luck I might get picked up / Camilla Chapman -- The original slut / Natalie Moore -- Untitled / Elizaveta Malsteva -- Megan / Elizaveta Malsteva -- Motherhood, the most punk rock thing you can do / Stephanie Guest -- Memories of my first orgasm as a teen / Deb -- Avenging Padmé Amidala / Trisha Jah -- L.M. Simpson, Frida, colour coding (vagina) / Luke Matthew Arnold -- Project Pussy stickers / Sarah Hibbs.
Cover title.
Blanket-stitched together together with red thread.
NLA's Nick Henderson Zine Collection copy is number 35/50.
Keywords: Women in popular culture; Women -- Identity; Punk culture; Feminism; Australian; Zines